Does yoga decrease cancer-related fatigue in women with breast cancer? Systematic review of randomized controlled trials - Morgan, Sergio Jiménez (International Journal of Research in Medical Sciences, 2017)
In its most recent report, the International Agency for Research on Cancer revealed that 1.7 million new cases of breast cancer were diagnosed worldwide in 2012, which represented almost 12% of all cancer types diagnosed in human beings that year. The purpose of the study was to determine if the practice of yoga allows decreasing cancer-related fatigue in women diagnosed with breast cancer. Methodology of the study was taken from database search on Web of Science, Embase, Pubmed, and Cochrane Library, as well as manual reference registration. The eligibility criteria were: (a) randomized controlled trials; (b) measurement of fatigue as main or secondary outcome; (c) studies published until December 2016; (d) studies published in English, Spanish, French or Portuguese. The guidelines of the PRISMA statement were followed. Methodological quality of randomized controlled trials was evaluated with the PEDro scale. Out of the 255 registers found, 14 randomized controlled trials were included. In half of the studies no statistically significant differences were found between experimental and control groups. Only four studies included had a comparative group besides a control group. All studies included were of moderate or high methodological quality according to PEDro scale. Findings suggest that yoga may not be effective to decrease cancer-related fatigue in women diagnosed with breast cancer.